The development of a quality improvement project to improve infection prevention and management in patients with asplenia or hyposplenia - O'Neill, Natalya Elizabeth (BMJ Open Qual, 2020)
Asplenia and hyposplenia (a/hyposplenia) are associated with increased morbidity and mortality from complications including infection. The recommended measures to reduce the risks associated with infection include patient education, vaccination and early initiation of antibiotic therapy for fever. Despite these recommendations, there is poor adherence to best practice management of patients with asplenia or hyposplenia (PWA/H). We present the development methodology and pilot data of a quality improvement project that explored whether a programme involving a novel medical alert card together with a patient and healthcare provider educational booklet increased vaccination rates and improved awareness and understanding of the infectious implications of a/hyposplenia. Our aim was to increase the proportion of those appropriately vaccinated and the proportion of patients with proper understanding of fever management by twofold in 18 months. Questionnaires were used locally as a root-cause-analysis to confirm the need for education and evaluate the effectiveness of the programme, as well as patient satisfaction. An interdisciplinary team developed a toolkit composed of a medical alert card and booklet. The toolkit was distributed to PWA/H who presented for a haematology clinic visit at a tertiary care centre. A separate set of questionnaires was then used to evaluate satisfaction and obtain feedback from patients and practitioners receiving the toolkit for the first time. Changes suggested by patients and practitioners with unanimous agreement among study investigators were made to the toolkit. The pilot study showed an increase in vaccination rates and awareness of vaccination status and appropriate fever management. The majority of the patients and practitioners found the information provided by the toolkit helpful. Given these promising single-centre findings, the intervention is being extended to another tertiary care centre with a large red blood cell disorders programme to evaluate its generalisability. The next step will be to expand the scope to paediatric PWA/H.